The The Word Formation Process of Suffixes in â€œLeave Beautifulâ€ Song Album by Astrid S. - Khusna, Febriana Aminatul; Fadilah, Dini Nurlaila (English Language Education, Universitas Internasional Batam, 2021)
Linguistics is the science that tries to understand the language from the perspective of its internal structure. The affix is the one of part I the linguistics study. The affix word is one of the vital things in a grammar. An affix serves to form meaning in a word. A suffix is an affix that is placed at the end of the word. This study aims to analyze the existence of the suffix in Astrid S.'s